(untitled) (Journal of the College of Basic Education, 2022)
Rhetoric plays an important role in secondary education because it helps to develop the expressive ability that reflects and develops the students’ personality and meets their needs and tendencies usually represented by self-confidence and self-realization. (Al-Rufu’: 2001, p. 9).